2010
DOI: 10.2519/jospt.2010.0304
|View full text |Cite
|
Sign up to set email alerts
|

Knee Pain and Mobility Impairments: Meniscal and Articular Cartilage Lesions

Abstract: The Orthopaedic Section of the American Physical Therapy Association presents this fifth set of clinical practice guidelines on knee pain and mobility impairments, linked to the International Classification of Functioning, Disability, and Health (ICF). The purpose of these practice guidelines is to describe evidence-based orthopaedic physical therapy clinical practice and provide recommendations for (1) examination and diagnostic classification based on body functions and body structures, activity limitations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 130 publications
(224 reference statements)
0
77
0
7
Order By: Relevance
“…42 Despite the minimally invasive nature, studies have shown that patients undergoing arthroscopic meniscectomy have pain, effusion, loss of range of motion (ROM), functional changes, neuromuscular and biomechanical changes, loss of quadriceps muscle strength, and a reduced quality of life. 5,8,12,13,27,30,31,33 Herrlin et al 17 showed that for middleaged patients with simple lesions in the meniscus, physical therapy has yielded T T STUDY DESIGN: Systematic review with metaanalysis.…”
mentioning
confidence: 99%
“…42 Despite the minimally invasive nature, studies have shown that patients undergoing arthroscopic meniscectomy have pain, effusion, loss of range of motion (ROM), functional changes, neuromuscular and biomechanical changes, loss of quadriceps muscle strength, and a reduced quality of life. 5,8,12,13,27,30,31,33 Herrlin et al 17 showed that for middleaged patients with simple lesions in the meniscus, physical therapy has yielded T T STUDY DESIGN: Systematic review with metaanalysis.…”
mentioning
confidence: 99%
“…El protocolo de la evaluación utilizada se basó en las recomendaciones de la APTA-Asociación Americana de Fisioterapia (Logerstedt et al, 2010), además de los modelos utilizados en otros estudios similares (Almosnino et al, 2014, Bryant, Pua, & Clark, 2009). …”
Section: Instrumentos Y Follow-upunclassified
“…These articles were not included in our review, as they did not report methods consistent with what is required to be included in a systematic review of the literature and therefore were graded as level V evidence. Clinical practice guidelines developed by the Orthopaedic Section of the American Physical Therapy Association 46 have systematically reviewed literature related to knee pain and mobility impairments associated with meniscal and articular cartilage lesions. Though these guidelines support the use of supervised rehabilitation that promotes progressive knee range of motion, progressive weight bearing, and progressive return to activity in those with articular cartilage lesions in the knee, they were not included in our review, as they included no specific discussion related to postoperative rehabilitation.…”
Section: Evidence Regarding Rehabilitation Protocols and Practice Guimentioning
confidence: 99%
“…46 Assessment of muscle performance may be quantified using measures of strength (peak force or torque), work production, power generation/absorption, rate of torque development, or fatigue protocols. It is common to compare side-to-side differences in muscle strength, as well as values between patient populations and controls.…”
Section: Functional Outcomes Related To Muscle Strengthmentioning
confidence: 99%